Mesopotamian Commentaries on the Diagnostic Handbook Sa-gig : a Edition and Notes on Medical Lexicography - Wee, John Z, (Cuneiform Monographs ;, 2019)
Mesopotamian Commentaries on the Diagnostic Handbook Sa-gig is intended for specialists in cuneiform studies, and includes a cuneiform edition, English translation, and notes on medical lexicography for thirty Sa-gig commentary tablets and fragments, as well as a study on technical notations recurring in these commentaries. Within the Cuneiform Monographs series, this book represents a companion volume to Knowledge and Rhetoric in Medical Commentary (Brill, 2019).